IN VITRO INDUCTION OF BLOOD MONONUCLEAR CELL PROLIFERATION BY ENDOGENOUS RETROVIRAL HERV-Eλ4-1 ENVELOPE PEPTIDE IN PATIENTS WITH MULTIPLE SCLEROSIS - A. A. Smagin; I. A. Goldina; K. V. Gaidul; M. S. Lubarsky (Медицинская иммунология, 2014)
A comparative in vitro study of blood mononuclear cells from multiple sclerosis patients and healthy donors was performed, in order to evaluate proliferative response to a retroviral antigen, aiming to determine immunomodulatory properties of synthetic oligopeptide homologous to a highly conserved human endogenous retrovirus HERV-Eλ4-1 envelope protein. It was revealed that this oligopeptide is able to stimulate the in vitro spontaneous and mitogen-induced proliferation of blood mononuclear cells from either donor and multiple sclerosis patients. Intensity of this oligopeptide-induced stimulatory effect depends on the protein concentration, and on initial level of blood immunocompetent cells proliferation. Hence, the endogenous retrovirus HERV-Eλ4-1 envelope region protein is able to increase functional activity of immunocompetent cells from human blood, that suggesting its immunostimulatory properties. It is possible that the mitogenic effects of this protein upon immunocompetent cells of multiple sclerosis patients represent a potential mechanism of retroviral involvement into pathogenesis of the disorder.